Urban Green Space Prioritization to Mitigate Air Pollution and the Urban Heat Island Effect in Kathmandu Metropolitan City, Nepal - Sabina Bhandari; Chuanrong Zhang (Land, 2022)
The rapid population growth and unplanned urbanization within Kathmandu Metropolitan City (KMC) have induced land use and land cover (LULC) changes that have exacerbated problems of air pollution and the Urban Heat Island (UHI) effect. These issues, as well as potential mitigations and possible counteractions, are currently under investigation by numerous research communities, resulting in various solutions being put forward including the creation of Urban Green Spaces (UGS). Establishing UGS would increase carbon dioxide extraction, minimizing photochemical ozone formation and liberation, while simultaneously cooling the microclimate of an area such as KMC. Optimized implementation of UGS throughout KMC requires an understanding of and prioritization of locations based on degraded air quality and the UHI effect. Unfortunately, such studies in these areas appear to be severely lacking, which has acted as a catalyst for this study. This research includes prioritization on two different spatial units—(i) at the administrative ward level and (ii) 0.0025° fishnet level. The result identifies the high-need locations where UGS establishment is recommended to mitigate air pollution and the UHI effect. Information obtained also heightened the existing UGS’s current sparsity and deplorable conditions. Findings from this study indicate that the utilization of rooftops are potential locations for new UGS, and enhancement of the existing UGS would prove to be an efficient use of currently underutilized spaces.